Development of novel aluminum matrix composite reinforced with hybrid filler (Fe3O4-SiC) for enhancement of magnetic, thermal, corrosion and mechanical properties - Ashrafi, Negin (2021)
In the present study, the hybrid reinforced magnetite; silicon carbide (Fe3O4-SiC) novel composite has been successfully fabricated by powder metallurgy method in the aluminum matrix. There is a demand in developing permanent magnetic composite with lightweight, corrosion resistance to develop the magnetic properties of aluminum matrix composites and obtain synchronization between electrical and thermal properties without mechanical degradation. Various researchers confirmed that Aluminum matrix composite (AMC) is an excellent multifunctional lightweight material with remarkable properties. However, to improve the wear resistance in the high-performance tribological application, hardness, and developing the corrosion resistance, magnetic, and thermal conductivity, optimized hybrid reinforcement of particulates magnetite, silicon carbide (SiC-Fe3O4) into an aluminum matrix needs to be examined. This study investigated the effect of adding 10, 15, 20, 30, 35 wt.% Fe3O4 and constant amount of 5 wt.% Mg saturate as a binder, and preparation and fabrication of hybrid metal matrix composite reinforced with constant amount of Fe3O4 (15, 30) wt. % and various silicon carbide particulates (10, 15, 20, 30) wt.% and 5 wt.% Mg as a binder. Commercially available pure aluminum powder, SiC, and Fe3O4 were used to fabricate through the powder metallurgy method. Mixed powders were mechanically milled for 2 h using a planetary ball mill, and compacted of blend powder at a load of 250 MPa, then sintered at a temperature of 600 °C. Field-emission scanning electron microscopy (FE-SEM), energy-dispersive x-ray (EDX), optical microscopy (OM), X-ray diffraction (XRD), VSM (Vibrating sample magnetometer) for magnetic properties, micro flash thermal conductivity, a four-probe system for measuring the electrical properties, mechanical properties (hardness, wear), potentiodynamic polarization measurements to investigate the corrosion behavior was used to evaluate hybrid reinforcements effects on aluminum. Adding SiC from 10 to 30 wt. % into Al-15 Fe3O4 slightly improved the saturation magnetization (Ms) from approximately 2 to 6 (emu/g). The addition of 30% wt. % ferrimagnetic Fe3O4 and 10 to 20% SiC nanoparticles into aluminum resulted in Ms between 5 to 11.058 (emu/g). Moreover, increasing the SiC 30 wt. % has improved the thermal conductivity of aluminum by 37%, while the electrical resistivity of the Al-Fe3O4-SiC composites increased by adding Fe3O4 and SiC. Hence, the addition of these reinforcements (Fe3O4-SiC) to the composite shows a positive outcome towards mechanical properties, corrosion resistance (low corrosion rate) to increase the durability and life span of material during operation. By comparing the magnetization, thermal conductivity, mechanical properties of all samples, the combination of Al-30Fe3O4-20SiC, can be selected as an optimization composite especially for magnetic applications, indicating 6.55 (emu/g) for saturation magnetization, and 10-5 (Ωm) for electrical resistivity. The thermal conductivity, hardness, and corrosion protection efficiency values have improved by 20%, 109%, 99.83% respectively. Moreover, the coefficient of friction (COF) is decreased by adding Fe3O4 and SiC hybrid composite in tribology behaviors, and the lowest COF is (0.412) for Al-30Fe3O4-20SiC which is developed by 31%.